Simple solve for X doesnt seem so simple
Showing the steps would be nice
8(x – 1) -2(7x + 10) – 16 = 0
Since it is only one term, you can multiply each factor's exponent by $\displaystyle -3$:
$\displaystyle (2x^2 y^{ - 2} z^{ - 1} x^{ - 1} )^{ - 3} = 2^{ - 3} x^{ - 6} y^6 z^3 x^3 = \frac{{x^{ - 3} y^6 z^3 }}
{8} = \frac{{y^6 z^3 }}
{{8x^3 }}
$
$\displaystyle (3x^3 + 6x^2 + 2x - 4) - (2x^3 - 4x^2 - 2x + 4) \to 3x^3 + 6x^2 + 2x - 4 - 2x^3 + 4x^2 + 2x - 4$$\displaystyle = x^3 + 10x^2 + 4x - 8$
$\displaystyle (2e^x + 3)(2e^x - 3) = \left( {2e^x } \right)^2 - 6e^x + 6e^x - 9 = 4e^{2x} - 9$